(untitled) (Research, Society and Development, 2022)
Essential food for the nutrition of children, breast milk is recommended by the World Health Organization (WHO) exclusively up to 6 months and in a complementary way up to at least 2 years of a half. breastfeeding is challenging and that the work of professionals in promoting breastfeeding is fundamental. to evaluate the impact that COVID-19 had on the adoption of breastfeeding by families of infants. This epidemiological, analytical, cross-sectional and retrospective study was carried out through medical records of a childcare outpatient clinic of a Child Friendly Hospital in Northeast Brazil. A total of 148 infants were evaluated and divided into two groups, one with children born until 2019 and the other with children born from 2020 onwards. AME) in the first consultation, while in the group born until 2019 the percentage was 8.82%. There was also a difference in the number of children who completed 6 months in exclusive breastfeeding, with 25% in children born until 2019 and 21.52% in those born in the Pandemic. It is concluded that there was a great impact on the adoption of breastfeeding in Brazilian families and that measures are urgently needed to encourage this practice and help to reduce the consequences in the pandemic period.